Biliary Atresia in Infants with Cholestasis - Budi Purnomo; Badriul Hegar (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2011)
Background: Cholestasis is a pathological condition due to impaired secretion and excretion of bile into the duodenum. The etiology should be found within golden period age ( 10 weeks of life) in order to get better outcome. Biliary atresia is characterized by total obstruction of extrahepatic biliary system. The cause is unknown. The only effective treatment is Kasai procedure, which should be done at 8 weeks age or less. The aim of this study was to observe the pattern of cholestasis cases in infants. Method: A descriptive study was conducted on 63 patients with cholestasis at the Harapan Kita Woman and Children Hospital, Jakarta between January 2008 and December 2009. Data was obtained from the computerized medical record database system. Statistical analysis was performed using SPSS program. Results: There were 63 infants, include of 40 (63.5%) boys. Age at admission were 80.2 (30-207) days. The laboratory findings included mean serum levels of hemoglobin 8.9 g/dL, conjugated bilirubin 12 mg/dL, alanine transaminase 149 u/L, aspartate transaminase 236 u/L, alkaline phospatase 582 u/L and gamma-glutamyl transpeptidase level 326 u/L. Biliary atresia was diagnosed in 8 (12.7%) infants by abdominal ultrasonography examination, cholangiography and liver biopsy. Kasai procedure (portoenterostomy) was performed to all those infants. Two of those infants died. Conclusion: Cholestasis has become one of the most common problem found in infants. Biliary atresia should always be considered as one of the cause, since early diagnosis and immediate treatment are needed to provide a good outcome. Keywords: cholestasis, biliary atresia, Kasai procedure